RESPON PERTUMBUHAN DAN HASIL TANAMAN KEDELAI AKIBAT PEMBERIAN PUPUK NPK DAN PUPUK GUANO - Elvrida Rosa; Bustami Bustami; Nazal Nofriadinal (Jurnal Agrotek Lestari, 2018)
The aim of this research is to get the appropriate dosage of NPK fertilizer and guano fertilizer and also to find out whether there is interaction between NPK fertilizer and guano fertilizer on the growth and yield of soybean crop. Implementation of the research was conducted in the experimental garden of Abulyatama University. Starting on March 8, 2017 until June 8, 2017. The design used is Group Random Design (RAK) with 3x3 factorial pattern with 3 replications. Factors studied are: a. NPK factor consisting of 3 levels: P0 (control), P1 (77 g / plot), P2 (84.7 g / plot). b: The factors studied were guano fertilizer consisting of 3 levels, namely: G0 (control), G1 (3.6 kg / plot), G2 (4.62 kg / plot). The observed parameters were plant height, number of pods, weight of pod perplot and weight of 100 seed of perplot. The results showed that NPK fertilizer treatment had no effect on all observations. While the treatment of guano fertilizer had a very significant effect on the number of pods per plant but no effect on plant height, weight of seed plot and weight of 100 seeds perplot. There is a significant interaction in the number of planting pods and the weight of 100 seeds perplot. Keywords: guano, NPK